PRODUCTION OF NANOCOMPOSITE FILMS OF PECTIN BASED ON COCOA PUREE WITH POTENTIAL USE AS PACKAGING FOR FOOD - Melo, Pamela Thais S. [UNESP]; Aouada, Fauze A. [UNESP]; Moura, Marcia R. de [UNESP] (Soc Brasileira Quimica, 2017)
The aim of this work was to produce biodegradable films based on the pectin and cocoa puree reinforced with chitosan nanoparticles. Nanoparticles were obtained by the ionotropic gelation. Films were produced according to the casting method, through a colloidal solution composed of water, cocoa puree, chitosan nanoparticles solution and different concentrations of pectin (2% and 3% w/w). Films were analyzed by thickness measurements, water vapor permeability, mechanical properties and scanning electron microscopy. Nanoparticles were characterized by zeta potential and showed spherical shape with a diameter of about 110 nm and zeta potential value of approximately +30 mV. Pectin 2% and 3% cocoa films exhibited tensile strength (mPa) of 15.1 +/- 0.7 and 22.9 +/- 1.6, respectively. After nanostructures addition, values increased to 25.2 +/- 0.7 and 29.8 +/- 1.3. Increasing concentration polymer and chitosan nanoparticles to improve tensile strength values. Films contained 3% of pectin exhibited more significant decrease in water vapor permeability values when chitosan nanoparticles were added, from 2.470 +/- 0.101 to 1.904 +/- 0.125 g mm / kPa h m(2). Results of the analyzes demonstrated that nanocomposites produced with pectin of different concentration showed satisfactory properties for application as packaging for food.
Keywords: edible films; chitosan nanoparticles; pectin